(untitled) (Research, Society and Development, 2020)
Smart cities represent innovative urban environments that make intensive use of Information and Communication Technologies (ICTs) which, together with the Internet of Things (IoT) paradigm, aim to increase efficiency in the provision of public services and enable citizens to have their demands met almost that in real-time. One of the main challenges of urban governance is public security, which emerges as an indispensable component for the city to achieve its strategic objective of improving the population’s living conditions. Given the above, this work had as main objective to develop a conceptual model of Smart and Safe City based on Self-Adaptive System (CISSA). For that, an exploratory and bibliographic research with a qualitative methodological approach was used. The construction of the CISSA model organized in three layers. Concept and demand layers address a specific definition of smart city and present a structure for the identification and classification of public security demands that contribute to provide guidelines on which the infrastructure layer through the self-adaptive system, monitors the environment and autonomously manages the system process of selecting solutions, adapting their behavior when necessary to solve public security challenges in the city. With the results obtained, it was realized that the CISSA model can guide city administrators in projects that seek to establish plans to make cities smarter and safer.